2012
DOI: 10.1128/jb.02013-12
|View full text |Cite
|
Sign up to set email alerts
|

The GTPase Activity of FlhF Is Dispensable for Flagellar Localization, but Not Motility, in Pseudomonas aeruginosa

Abstract: The opportunistic human pathogen Pseudomonas aeruginosa uses two surface organelles, flagella and pili, for motility and adhesion in biotic and abiotic environments. Polar flagellar placement and number are influenced by FlhF, which is a signal recognition particle (SRP)-type GTPase. The FlhF proteins of Bacillus subtilis and Campylobacter jejuni were recently shown to have GTPase activity. However, the phenotypes associated with flhF deletion and/or mutation differ between these organisms and P. aeruginosa, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 43 publications
1
64
0
Order By: Relevance
“…Previous studies have shown that both P. aeruginosa PAK and P. putida became polar multi-flagellates when FlhF was overexpressed (Pandza et al, 2000; Schniederberend et al, 2013). Since FlhF and FleN are binding partners (Balaban and Hendrixson, 2011; Kazmierczak and Hendrixson, 2013; Kusumoto et al, 2006; Murray and Kazmierczak, 2006), it is possible that if their interaction is hampered by the fleN mutations, the cells may be experiencing a relatively higher activity of FlhF.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that both P. aeruginosa PAK and P. putida became polar multi-flagellates when FlhF was overexpressed (Pandza et al, 2000; Schniederberend et al, 2013). Since FlhF and FleN are binding partners (Balaban and Hendrixson, 2011; Kazmierczak and Hendrixson, 2013; Kusumoto et al, 2006; Murray and Kazmierczak, 2006), it is possible that if their interaction is hampered by the fleN mutations, the cells may be experiencing a relatively higher activity of FlhF.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we could provide evidence that Sp FlhF and Sp FlhG interact in vitro and that the N‐terminal section of Sp FlhG stimulates the GTPase activity of Sp FlhF. Thus, Sp HubP‐mediated interaction between FlhF and FlhG and control of the GTPase activity might affect FlhF‐related functions such as polar accumulation and recruitment of flagellar components, but also flagellar performance, as has recently been suggested for P. aeruginosa (Schniederberend et al ., ). Accordingly, a deletion of hubP in both V. cholerae and S. putrefaciens CN‐32 resulted in a significantly decreased ability to navigate through soft agar.…”
Section: Discussionmentioning
confidence: 97%
“…Clean deletions confirmed that all three genes were necessary for normal swimming, and for polar placement of the flagellum. The GTPase FlhF was previously considered the topmost component in the polar localization hierarchy for the flagellum of P. aeruginosa, controlling not just localization, but also function (Kazmierczak and Hendrixson, 2013;Schniederberend et al, 2013). However, FlhF has now been dethroned by the Poc complex, as a FlhF-GFP fusion traded its wild-type bipolar localization for non-polar sites -correlated with the positions of non-polar flagella -when any of TonB3, PocA or PocB was missing.…”
mentioning
confidence: 99%